2021
DOI: 10.47191/ijsshr/v4-i5-03
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Covid-19 Lockdown on Socio-Economic Conditions of Semi-Skilled Returnee Migrant Workers of Bangladesh

Abstract: The study explores immediate impact of COVID-19 lockdown on socio-economic conditions of the returnee migrants in Bangladesh. Using digital platform the study collects primary data through survey on returnee migrants of Bangladesh, and it follows descriptive mode of analysis. The study finds that the majority of the returnee migrant’s family members are dependent on the remittance. The workers return home because of the shutting down of their income sources due to a prolong period of lockdown. After returning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…It was noted from available researches, although women performed key roles in agricultural activities, that due to local societies and customs, they were treated differently as compared to men. Females were facing social exclusion in terms of less control and access over land, income, livestock, local patriarchal system, agricultural resources, land, jewelry, and money (Eneyew & Mengistu, 2013;Jahan, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was noted from available researches, although women performed key roles in agricultural activities, that due to local societies and customs, they were treated differently as compared to men. Females were facing social exclusion in terms of less control and access over land, income, livestock, local patriarchal system, agricultural resources, land, jewelry, and money (Eneyew & Mengistu, 2013;Jahan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because of the local customs, violence against women, and a lack of awareness about gender-related government interventions, women faced double marginalization, for being women and for being pastoralists. Jahan (2018) enquires about the current condition of working women in Khankhanapur, village of Rajbari, Bangladesh. The economy of the country is mainly based on agriculture, and the majority of women are related to agricultural production directly or indirectly.…”
Section: Women Inequality In Agriculturementioning
confidence: 99%
“…As per the findings of the study, those migrants who have a low level of savings and merely tangible or intangible resources have also moved to their village as a result of losing their employment. Semi-skilled workers are referred to as “the workers who have moderately broad knowledge and practical skills and solve regular problems by using simple techniques under supervision but autonomy to a certain degree” [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…A survey on migrant workers in Vietnam [ 10 ] showed that approximately 37% returned home with savings, and most of the returnee workers [ 55 ] spent their savings to survive during the lockdown. Based on the findings, a study by Dhaka Tribune [ 56 ] reported that while 34% of returnees reported having sufficient resources to finance living expenses for up to three months, 33% reported having no savings at all [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation